The Nutritional Status of Children Receiving Local Supplementary Feeding at Tawangrejo Public Health Center, Madiun - Komalawati, Dewi; Setyobudi, Sugeng Iwan (Universitas STRADA Indonesia, 2025)
Undernutrition among under-five children remains a major public health issue in Indonesia, particularly underweight which contributes to growth failure and increased morbidity. According to the 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of underweight in children is still above the national target, including in East Java. Locally-based supplementary feeding (LSF) is one of the strategies to address this problem, as it not only provides additional energy and protein but also involves nutrition education for parents to improve feeding practices. This study aimed to evaluate the effect of LSF on the nutritional status of underweight children under five at Tawangrejo Health Center, Madiun. An evaluative survey with a one-group pretest-posttest design was conducted involving 30 children aged 12–59 months (W/A < -2 SD). Intervention was carried out for 28 consecutive days with LSF menus containing an average of 318 kcal and 22.2 g protein per portion. Body weight and height were measured at baseline and post-intervention, and nutritional indices were analyzed using paired t-tests. Significant improvements were observed in body weight (mean +0.47 kg, p = 0.0001), height (mean +0.61 cm, p = 0.000), W/A z-score (p = 0.007), H/A (p = 0.042), and W/H (p = 0.001). Local-based supplementary feeding effectively improved the nutritional status of underweight children, suggesting its potential as a community-based strategy to reduce undernutrition in Indonesia